Quantitative and Qualitative Evaluation of Four Choice Questions In Shahroud University of Medical Sciences During 2021-2022 - sahar Paryab; Robabeh Zarouj Hosseini; sepehr Zamani; masomeh lashkari; maryam Yousefi; kimia Zarouj Hosseini; omid Garkaz (Babol University of Medical Sciences, 2023)
Background and Objective: Any test as a measurement tool must have sufficient validity and reliability to measure the desired attribute. Multiple-choice tests are the most common types of tests in medical education, which have a high degree of reliability, and this study was conducted with the aim of quantitative and qualitative evaluation of four-choice questions in Shahroud University of Medical Sciences in the academic year of 2021-2022. Methods: This descriptive study was conducted on all General and specialized courses in the two academic years of 2021-2022 at the Shahroud University of Medical Sciences. For the quantitative evaluation of the questions (difficulty index and discrimination index), the Hamava system was used and for the qualitative evaluation, the 14-item checklist of Millman was used. Findings: This study showed that out of 5000 examined questions, 2569 questions (51.4%) had a simple difficulty coefficient and 2500 (50%) had a suitable clean coefficient. And the average standard deviation of the degree of difficulty was 0.700±0.314 and the degree of cleanliness was 0.625±0.247, also 330 questions (48.5%) of taxonomy two and 190 questions (27.9%) were without defects. The most types of defects were the absence of most of the information in the question stems of 196 questions, the presence of negative words in the question stems of 136 questions, and the presence of options for all items in 121 questions, none in 45 questions, and combined options in 34 questions. And in the structure of question 398 (58/1%) was the most type of defect. Conclusion: To improve the quality of tests and use the results of quantitative and qualitative analysis of questions, practical solutions should be thought of, and professors should be trained in designing and using appropriate questions and preparing for-choice question banks.